Evaluating The CURB-65 Score for Prognostic Assessment in COVID-19 Patients: A Systematic Review - Astiarani, Yunisa; Sari, Gabriella Aninda Puspita; Kristian, Kevin (School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, 2025)
Introduction: Several instruments and biomarkers have been used to assess the severity and predict outcomes in COVID-19 patients, each with varying sensitivity levels. One such tool is the CURB-65 score—an acronym for Confusion, Urea nitrogen, Respiratory rate, Blood pressure, and age ≥65 years—which has traditionally been used to evaluate the severity of community-acquired pneumonia. Its application in COVID-19 patients aims to identify clinical deterioration and assist in risk stratification. Accurate prognosis is essential to guide clinical management and reduce mortality. However, the utility of the CURB-65 score in predicting outcomes in COVID-19 patients remains a subject of debate. This study aims to evaluate the performance of the CURB-65 score in determining the prognosis of patients with COVID-19. Methods:This systematic review was conducted in accordance with PRISMA guidelines. Relevant studies published between 2020 and 2022 were identified through searches using predefined keywords in PubMed, ScienceDirect, and EBSCO databases. Studies of all designs that assessed the CURB-65 score concerning COVID-19 outcomes were considered for inclusion. Results: Ten studies were included in this review, evaluating the CURB-65 score's effectiveness in predicting various outcomes in COVID-19 patients, including overall mortality, 30-day mortality, adverse outcomes, need for organ support, ICU admission and intervention, critical illness, mechanical ventilation, and 72-hour mortality. Seven out of ten studies demonstrated good prognostic performance of the CURB-65 score, with sensitivity greater than 80% or an Area Under the Curve (AUC) exceeding 0.80 for predicting mortality. Conclusion: The CURB-65 score shows promising utility in predicting mortality among COVID-19 patients and may perform better than several other prognostic tools. Its simplicity and accessibility make it a valuable aid in clinical decision-making, although further validation in different populations may be warranted.